OH density and water vapor concentration gradients during plasma-droplet interactions - Wang, Jianan; Nayak, Gaurav; Bruggeman, Peter J. (Frontiers in Physics, 2025)
Plasma-droplet interactions significantly promote the reactivity transfer of gas phase species from the plasma to the liquid phase. Nonetheless, experimental studies on the impact of droplet evaporation on reactive species generation in such systems remain scarce. We report the spatial distribution of water vapor and OH radical densities around a droplet (∼41 μm in diameter) in He and He-Ar plasma using laser-induced fluorescence. The results reveal a significant gradient in both water vapor and OH radical concentrations near the droplets. Mutiple droplets present in the plasma can lead to a significant accumulation of water vapor and even local quenching of the discharge. The findings are critical for developing a quantitative understanding of plasma-liquid interactions for a broad range of plasma-enabled applications in the liquid phase often involving OH radicals.